Coexistence of Immune Checkpoint Inhibitor-Induced Autoimmune Diabetes and Pancreatitis - Zhang, Amy L.; Wang, Fang; Chang, Lee-Shing; McDonnell, Marie E.; Min, Le (Frontiers in Endocrinology, 2021)
Autoimmune diabetes is a rare but severe endocrine toxicity induced by immune checkpoint inhibitor (ICI) treatment. It is unclear if ICI causes selective islet toxicity or non-selective pancreas toxicity. We analyzed 11 patients treated with ICI who developed ICI-related autoimmune diabetes. Eight patients had lipase and/or amylase tested on the same day of diagnosis of autoimmune diabetes. Among them, 75% (6/8) had normal lipase and 100% (6/6) had normal amylase. There was no correlation between glucose level at onset and biochemical pancreatitis. We characterized the clinical features of ICI-induced autoimmune diabetes. Fifty-five percent (6/11) of patients tested positive for GAD65 autoantibodies, and 55% (6/11) developed diabetic ketoacidosis at manifestation of hyperglycemia. In all 11 patients, C-peptide levels were low in the presence of hyperglycemia. ICI-induced thyroiditis was found in 64% (7/11), of which 36% (4/11) were newly diagnosed with thyroiditis while the remaining 27% (3/11) had pre-existing hypothyroidism followed by ICI-induced thyroiditis. Additionally, 27% (3/11), developed ICI-induced hypophysitis. Thyroiditis and autoimmune diabetes coexisted in all patients with ICI-induced hypophysitis. The median time from ICI treatment to the onset of autoimmune diabetes was 11 weeks. Our data suggest that few patients had coexistent ICI-induced autoimmune diabetes and pancreatitis, suggesting ICI mainly caused selective islet toxicity.